2008
DOI: 10.1111/j.1524-4725.2008.34204.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Erbium:YAG (2,940-nm) Laser for Fractional Ablative Photothermolysis in the Treatment of Photodamaged Facial Skin: A Pilot Study

Abstract: Fractional ablative photothermolysis using erbium:YAG laser (2,940 nm) is a promising option for skin resurfacing with reduced risk and downtime compared to existing laser methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 15 publications
0
49
0
Order By: Relevance
“…Bodendorf et al [18] found no difference between both modalities based on the published material and their own experience; this conclusion is in complete agreement with our own results. As for ablative fractional methods in general, the efficacy of various laser modalities for rhytide reduction has been demonstrated (e.g., [2,5,12,13,15,17,18]) but the effect of a single treatment session may not be comparable to conventional ablative methods. There is published material opposing this statement; for instance, Trelles et al [14] published very encouraging results about a single treatment with a fractional Er:YAG laser, albeit in a very inhomogeneous sample in terms of treated region and treatment parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bodendorf et al [18] found no difference between both modalities based on the published material and their own experience; this conclusion is in complete agreement with our own results. As for ablative fractional methods in general, the efficacy of various laser modalities for rhytide reduction has been demonstrated (e.g., [2,5,12,13,15,17,18]) but the effect of a single treatment session may not be comparable to conventional ablative methods. There is published material opposing this statement; for instance, Trelles et al [14] published very encouraging results about a single treatment with a fractional Er:YAG laser, albeit in a very inhomogeneous sample in terms of treated region and treatment parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The findings about ablative fractional photothermolysis of rhytides that have been published so far are encouraging, but they are inconsistent in detail as far as study design and the respective efficacy of different laser modalities are concerned. Whereas several studies claim encouraging results of erbium lasers (e.g., [12][13][14]), the same holds true for fractional CO 2 ablation [15][16][17]. There is very little evidence on the comparative safety and efficacy of both methods, but the limited scope of the literature to date suggests a roughly equivalent status [18], just as it does for non-fractional applications [4][5][6][7].…”
Section: Introductionmentioning
confidence: 94%
“…Except for one case of hyperpigmentation in a phototype IV patient, no side effects were observed. Two further studies confirmed that microfractional ablative treatment with 2,790 nm and 2,940 nm erbium lasers is a safe and effective treatment for wrinkle reduction and results in only minimal patient downtime [38][39][40]. Supporting data have recently been published by Berlin et al Ten patients, Fitzpatrick skin types I-III, with photodamaged facial skin were given a single-pass superficial full-face ablative treatment using the CO 2 laser at energy levels of 80-100 mJ.…”
Section: Non-ablative Fractional Photothermolysis Lasermentioning
confidence: 99%
“…Fractional ablative procedures are available with carbon dioxide laser (CO 2 laser, 10,600 nm) and erbium YAG laser (Er:YAG laser, 2,940 nm) [3][4][5]. The concept of AFR has so far been used for dermal remodeling in the treatment of photodamaged facial skin, rhytides, acneiform scarring, and burn scar remodeling [3,[6][7][8][9][10]. Theoretically, AFR may also facilitate penetration and distribution of topically applied drugs, since the ablated laser holes extend into dermis, thereby possibly acting as channels for drug uptake.…”
Section: Introductionmentioning
confidence: 99%